2021
DOI: 10.3390/molecules26206132
|View full text |Cite
|
Sign up to set email alerts
|

Direct Conversion of 3-(2-Nitroethyl)-1H-Indoles into 2-(1H-Indol-2-yl)Acetonitriles

Abstract: The recently discovered [4+1]-spirocyclization of nitroalkenes to indoles provided a convenient new approach to 2-(1H-indol-2-yl)acetonitriles. However, this reaction was complicated by the formation of inert 3-(2-nitroethyl)-1H-indole byproducts. Herein, we offer a workaround this problem that allows for effective transformation of the unwanted byproducts into acetonitrile target molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…To the best of our knowledge, there is only one direct approach to structure 4 reported recently by Yan et al [ 18 ] that involves oxidative ring-opening/cyclization cascade of indoles 1 with the 1,2-diaminoarenes 3 ; this rather elegant method relays on initial oxidation of indole with NIS in DMSO to obtain 3 H -indol-3-one 2 , which undergoing subsequent ANRORC cascade with bis-nucleophilic species 3 ( Scheme 1 ) [ 18 ]. In turn, we recently demonstrated that nitroolefins might act as 1,4-CCNO dipoles in reaction with indoles in the presence of phosphorous acid; this unusual transformation efficiently leads to the formation of stereo-defined spirocyclic scaffolds 5 , which are versatile and affordable synthetic equivalents of highly functionalized indoles [ 19 , 20 ]; it was shown that upon treatment with mild acids or bases as well as under neutral condition upon heating ( Scheme 1 ) spiranes 5 could be diastereoselectively transformed into 2-(3-oxoindolin-2-yl)-2-arylacetonitriles 6 [ 21 , 22 ]. Further extrusion of 2-phenylacetonitrile molecule followed by the formation of postulated intermediate 2 was used by us to design cascade sequence involving 1,2-aryl shift and leading to 3-hydroxyindolin-2-ones 9 ( Scheme 2 ) [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there is only one direct approach to structure 4 reported recently by Yan et al [ 18 ] that involves oxidative ring-opening/cyclization cascade of indoles 1 with the 1,2-diaminoarenes 3 ; this rather elegant method relays on initial oxidation of indole with NIS in DMSO to obtain 3 H -indol-3-one 2 , which undergoing subsequent ANRORC cascade with bis-nucleophilic species 3 ( Scheme 1 ) [ 18 ]. In turn, we recently demonstrated that nitroolefins might act as 1,4-CCNO dipoles in reaction with indoles in the presence of phosphorous acid; this unusual transformation efficiently leads to the formation of stereo-defined spirocyclic scaffolds 5 , which are versatile and affordable synthetic equivalents of highly functionalized indoles [ 19 , 20 ]; it was shown that upon treatment with mild acids or bases as well as under neutral condition upon heating ( Scheme 1 ) spiranes 5 could be diastereoselectively transformed into 2-(3-oxoindolin-2-yl)-2-arylacetonitriles 6 [ 21 , 22 ]. Further extrusion of 2-phenylacetonitrile molecule followed by the formation of postulated intermediate 2 was used by us to design cascade sequence involving 1,2-aryl shift and leading to 3-hydroxyindolin-2-ones 9 ( Scheme 2 ) [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…With a working protocol for the formation of the target 4-quinolones at hand, we then focused on developing a procedure for the N -alkylation of the free, unsubstituted indolinone 2a-H . From our experience, while N -functionalized precursors 2 can be obtained directly 14 or by a two-step procedure 54 from the corresponding N -alkylated indoles 8 (Scheme 4b and 4c) the yields are generally quite low (20–30%) compared to their N–H congeners (50–90%). Therefore, a reliable and practical method of N -alkylation of indolinones 2 would be highly desirable.…”
Section: Table 1 Search For a Base To Promote Indolinon...mentioning
confidence: 99%
“…The pursuit of this kind of transformation have started several years ago once we have learned a reliable, direct way to 2,2-disubstituted 3-indolinones 2 via acid-catalyzed reaction between nitroalkenes 7 and indoles 8 (Scheme 4b ). 14 There are the other available options as well, either via intermediate spirocyclic indolines 9 52 53 or via nitroethylindoles 10 54 (Scheme 4a and 4c, respectively), but both of them, while not particularly tedious, require an extra chromatography purification step.…”
Section: Table 1 Search For a Base To Promote Indolinon...mentioning
confidence: 99%
“…17 Nitriles 8 could also be efficiently prepared directly from 1 and 2 via a one-pot reaction. 18 Taking into account the stereo-controlled nature of these transformations, we were interested in developing synthetic methods utilizing such nitriles as a versatile synthetic platform for the preparation of various functionalized indole derivatives for drug discovery.…”
mentioning
confidence: 99%
“…Initially, under mild conditions, spiro­[indole-3,5′-isoxazoles] 7 were formed in high yields (Scheme ), which could be further transformed into single diastereomers of 2-(3-oxoindolin-2-yl)-2-arylacetonitriles 8 upon heating with tertiary amines in the presence of H 3 PO 3 or at room temperature (Scheme ). Nitriles 8 could also be efficiently prepared directly from 1 and 2 via a one-pot reaction . Taking into account the stereo-controlled nature of these transformations, we were interested in developing synthetic methods utilizing such nitriles as a versatile synthetic platform for the preparation of various functionalized indole derivatives for drug discovery.…”
mentioning
confidence: 99%